(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
The objective of this study was to optimize the parameters for the development of refused derived fuel (RDF) pellets from municipal solid waste (MSW) and rice husk by using Response Surface Methodology (RSM). In this a systematic study was conducted, where three parameters were varied according to RSM factorial design. The binder concentration (5-10%) pressure (700-1200 psi) and retention time (3-7 minutes) were used for RDF pellet development under hydraulic press, measured hardness bulk density (BD) and durability (DU). The T3 treatment results revealed the highest pellet hardness, bulk density, and durability 25 kg, 805 kg/m3, 99% respectively by application binder concentration (5%), pressure (1200 psi) and retention time (5 minutes). The experimental data on response variables were fitted into quadratic polynomial model using the multiple regression analysis and found that it was statistically significant quadratic model. The RDF physical chemical and mechanical characteristics were also evaluated and found their relationship between HHV, carbon, ash, DU, BD and energy density. The ash contents were inversely proportional to DU and HHV whereas DU was directly related to BD. Bangladesh J. Sci. Ind. Res.54(4), 329-338, 2019